Radiotherapy and Immunotherapy for Head and Neck Cancer: Current Evidence and Challenges - Qian, Jack M.; Schoenfeld, Jonathan D. (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICI) have revolutionized cancer treatment over the past decade. However, although the immune landscape suggests a strong rationale for the use of these agents in patients with head and neck squamous cell carcinoma, the available clinical evidence indicates that most patients currently do not respond to ICI monotherapy. Radiotherapy is a primary treatment modality for many patients with locally advanced head and neck cancer. While ionizing radiation traditionally has been thought to act in a purely cytotoxic fashion, a growing body of preclinical studies have demonstrated additional profound immunomodulatory effects. Consequently, there has been a surge of interest in the potential synergy between radiotherapy and immunotherapy, both the potential for radiotherapy to augment the systemic anti-tumor immune response and the potential for immunotherapy to improve in-field tumor response to radiation. In this review, we summarize the current preclinical and clinical evidence for radioimmunotherapy, with a particular focus on studies directly relevant to head and neck squamous cell carcinoma, as well existing challenges and future directions for this emerging field.